2009
DOI: 10.1007/s10584-009-9626-y
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated afforestation of the Sahara and Australian Outback to end global warming

Abstract: Each year, irrigated Saharan-and Australian-desert forests could sequester amounts of atmospheric CO 2 at least equal to that from burning fossil fuels. Without any rain, to capture CO 2 produced from gasoline requires adding about $1 to the per-gallon pump-price to cover irrigation costs, using reverse osmosis (RO), desalinated, sea water. Such mature technology is economically competitive with the currently favored, untested, power-plant Carbon Capture (and deep underground, or under-ocean) Sequestration (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 65 publications
7
82
1
Order By: Relevance
“…Recently, Ornstein et al (2009) investigated this idea in desert regions on a global scale. Using a global climate model, they simulated large-scale reductions of surface temperature in the Sahara and the Australian desert.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ornstein et al (2009) investigated this idea in desert regions on a global scale. Using a global climate model, they simulated large-scale reductions of surface temperature in the Sahara and the Australian desert.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found that their models predicted a large increase in precipitation in desert regions and related this to the Charney effect (Charney, 1975). With respect to irrigation, Ornstein et al (2009) stated that the extremely valuable aquifers, which are available in some desert regions, should not be further exploited but considered instead the application of recent advances in desalination technology such as reverse osmosis. They discussed the costs and technological requirements to realize such a large-scale, international project covering areas of the order of 10 9 ha.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, another SENCH-related solution that we have proposed, "Irrigated Afforestation of the Sahara and Australian Outback to End Global Warming" (Ornstein et al 2009) could be initiated to renewably sequester about 8 additional GtC/yr. We had suggested CCS or nuclear-fission to power the sea-water desalination plants and pumps needed to supply fresh irrigation water to the 'desert forests'.…”
Section: Discussionmentioning
confidence: 99%
“…When a previously barren area (NPPo = 0, cl1 = 0, cl2 = 0) is afforested or put into sustainable agricultural production, the total CO 2 -footprint/yr will be about (m tC/ha/yr − NPPn tC/ha/yr), even if not harvested, because all net production is above the zero barren baseline. So long as m is small, this can provide a very substantial decrease in atmospheric CO 2 (see Ornstein et al 2009). productivity (NPP) is defined as the difference between the carbon sequestered through photosynthesis and the carbon released as CO 2 due to respiration. Thus, when decay of the fallen trees is prevented, the harvest itself represents an increase in NPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation